Sport, lexicon and history: considerations about the Italian sports language - Janeli, Thais Bonfim [UNESP]; Orsi, Vivian [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2023)
This work brings considerations about previous research (JANELI, 2021) and reflects on lexical items found in the Italian journalism sports language, specifically loan words or neologisms. To this end, a corpus was assembled, based on news from the portal Tuttosport, between 2018 and 2019. Based on Lexicology, Lexical Semantics and Neology, through AntConc software, we have compared data in three Italian dictionaries and then we have checked the occurrence of lexias in a control corpus. We aim to present information from the context of use and with the addition of morphological and semantic information. Finally, we emphasize a historical fact of forbidden use of foreign words in sport, during the fascist period, in Italy.
Keywords: Lexicology; Lexical Semantics; Neology; Sports Journalistic Language; Italian Language